Bất định chính sách kinh tế, phát thải carbon, và hiệu suất của doanh nghiệp: Nghiên cứu tại Châu Á - Lê Anh, Tuấn; Nguyễn Hà Phước , Trọng; Hồ Mỹ , Thiện (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This paper investigates the effect of economic policy uncertainty on carbon emission intensity and its economic significance for firm performance in five countries within the Asia region. Based on a dataset comprising 21,501 observations from the period 2002 to 2022 and employing two-step System-GMM regression, the study finds that economic policy uncertainty is positively correlated with firms’ carbon emission intensity. This effect is more pronounced for firms operating in countries with poor control of corruption. Furthermore, facing economic policy uncertainty significantly reduces the performance of firms with high emission intensity.
Keywords: Economic policy uncertainty; Corporate carbon emission; Firm performance